Electrocardiographic Abnormalities of Takotsubo Cardiomyopathy in a Patient with Paced Ventricular Rhythm - Krati Chauhan; Siva P. Sontineni; Venkata M. Alla; Mark J. Holmberg (Cardiology Research and Practice)
Takotsubo cardiomyopathy (TCM) is a unique cardiomyopathy characterized by chest pain, ECG, and regional wall motion abnormalities closely mimicking acute myocardial infarction, in the absence of significant coronary artery disease. Classic ECG changes of TCM include ST elevation or T wave inversion. However, ECG abnormalities of TCM in patients with paced ventricular rhythms have not been well characterized. Herein, we report the case of an 85-year-old pacemaker dependant female who was diagnosed with TCM four weeks following the demise of her husband. Abnormal negative T wave concordance in precordial leads and QT interval prolongation were the only new ECG findings and these reverted back to baseline on followup.